The Tale of Iskander” – a poem of covenants and teachings - Бисенбaев П.; Сaғындықов Н. (Journal of Oriental Studies, 2018)
A special place in the world literature is occupied by poem-legends about Iskander Dvirog. It is well known that his image is embodied even in “Koranic legends” and in the poem “Kissas-ul-Ambiya”. The Muslim peoples were acquainted with the stories about Iskander through themes often used in the works of Firdausi, Nizami, Amir Khosrow, Navoi and other Eastern classics. In all of the East, these legends became known as Iskander-name. And, although the theme of all these works was central, the ideas expressed in them, the problems raised in them and the system of events are completely different from each other. Therefore, each of these names was the engine of the actual problems of their environment, their time. Of course, within the framework of one article it is impossible to fully cover all written by the above-mentioned Eastern poets. Therefore, it will be right to consider works by such authors as Firdausi (“Shakhname” describing Iskander) and Nizami (“Iskander-name”) in the same row. Researchers of the above-mentioned works conduct an artistic search in the study of such problems as poverty and deprivation, serving people, fighting against violence, life and death, freedom and happiness of man. They come to the conclusion that the poems “Iskander-name” is a poem of covenants and teachings, giving the rulers wisdom of government